Influence of the bypass on the capacity of roundabout crossings - Slabý, Petr (Univerzita Pardubice, 2010)
Capacity of standard roundabout crossings is calculated after the Czech Manual TP 135. Micro– simulation model VISSIM has been used to evaluate the influence of the modification of the crossing – the use of bypass. The increase of roundabout capacity for 20 and 50 % of cars turning into bypass is presented. Naturally the impact of bypass is more pronounced for larger parts of turning cars. Similar graphs for other dispositions could serve as an amendment for designers of these crossings.
Keywords: roundabout crossings; capacity; bypass; micro-simulation; VISSIM